Collaborative Governance in Fulfilling the Right to Education for Children of Non-Document Migrant Workers in Malaysia - Suci Widiawati; Ardhana Januar Mahardhani; Hadi Cahyono; Sulton Sulton; Ikhwan Fauzi Nasution (Universitas Sultan Ageng Tirtayasa, 2023)
This article aims to look at the government's role in fulfilling the right to basic education for the children of undocumented migrant workers in Malaysia. The research was conducted in the Kepong area of Selangor, Malaysia, with a qualitative method. Sources of data using primary and secondary data and data collection using observation, interviews, and documentation. The results obtained in this study show that the government has not been able to fulfill basic education rights for the children of migrant workers, especially those who do not have documents. The government is coordinating with community organizations, one of which is Muhammadiyah, to set up a guidance center that provides education rights for children of Indonesian migrant workers who do not have documents under the control of the Kuala Lumpur Indonesian School.